Distribution Patterns and Accessibility of Health Facilities Analysis Using Geographic Information Systems (GIS) in Badung District, Indonesia - Nafisa, Syahla Yuma; Hadibasyir, Hamim Zaky; Sigit, Agus Anggoro; Wibowo, Afif Ari; Sasmi, Annisa Trisnia (GEOGRAPHIA : Jurnal Pendidikan dan Penelitian Geografi, 2024)
Badung District is located in Bali Island, a famous and most-visited island tourists destination in Indonesia. Tourists generally understand that health is one of the important things in their lives, as well as the need for travel. The problem found is that the public does not fully comprehend the details regarding the location of the health centre, both the address and reliable contact person. In an emergency, people find it difficult to know the location of the nearest health centre so they can get treatment and service quickly. In this research, qualitative descriptive research was used, based on secondary data. The Average Nearest Neighbor method was used as the data analysis method to analyze the distribution pattern of health facilities in Badung Regency, aimed to determine the distribution pattern of health facilities in Badung Regency. The results of the calculation revealed the Nearest Neighbor Ratio value of 1.055839 or T= 1.055839. It showed that the distribution pattern of health facilities in Badung Regency was random. The accessibility of health centre health facilities to settlement areas was highest in the Abiansemal sub-district with a coverage area of 22.33 km2, of which the settlement area was 65.52 km2 or 34%, while the lowest coverage was in the Petang sub-district with 1.75 km2 and an area settlements of 91.98 km2 or 2.67%. The highest accessibility of hospital health facilities was in the Kuta District area with a coverage area of 21.16 km2 with a settlement area of 8.8 km2 or 32.25%.